Clinical study, network pharmacology, and molecular docking of Kunxian capsule in treating idiopathic membranous nephropathy - Lv, Jia; Gao, Xinyu; Liu, Lihua; He, Libing; Tian, Geng; Lu, Xuehong (Frontiers in Medicine, 2025)
ObjectiveA new Tripterygium wilfordii preparation called Kunxian capsule (KX) has been approved in China. However, it is still unknown whether KX is safe and effective for idiopathic membranous nephropathy (IMN) and its therapeutic mechanism of action is unclear.MethodsWe conducted a retrospective study of 39 patients with IMN who received KX to investigate its efficacy and side effects of KX in treating IMN. We also used network pharmacology and molecular docking methods to explore the potential mechanism of action of KX in IMN.ResultsIn patients with IMN receiving KX treatment, 24 h urine protein was markedly decreased, whereas serum albumin levels increased. The overall clinical response rate was 79.49% after 6 months of treatment, and there were no significant adverse events. Quercetin, luteolin and kaempferol were the main bioactive ingredients of KX in treating IMN. AKT1, IL6, and TNF were core targets. The main potential mechanism of KX in treating IMN were pathways involved in cancer, the AGE-RAGE signaling pathway in diabetic complications, lipid and atherosclerosis. Molecular docking results showed that the binding force between the active ingredient and core target was relatively stable.ConclusionKX is a safe and effective treatment option for IMN and can effectively improve serum albumin and 24 h urine protein levels in patients with IMN. This study preliminarily reveals the possible mechanism of KX in the treatment of IMN and provides a theoretical basis for future clinical research.